Design and Characterization of Sugar-Based Deep Eutectic Solvents Using Conductor-like Screening Model for Real Solvents - Silva, Liliana P. (2018)
Inspired by the lack of characterization of natural eutectic and deep eutectic (DES) systems, we studied the solid-liquid equilibria (SLE) of binary and ternary mixtures involving choline chloride and sugars. The densities, viscosities and solvatochromic parameters for the binary systems containing choline chloride, [Ch]Cl, were measured at the eutectic composition, and the water impact on these properties was also investigated in order to address the tailoring of their properties using water. Mixtures of sugars are shown to present an ideal behavior, while their binary mixtures with choline chloride present negative deviations to the ideality, particularly in the sugar solubility curve. Aiming to develop a predictive model to design new sugar based DES, the [Ch]Cl + sugars phase diagrams were used to tune the COnductor-like Screening MOdel for Real Solvents (COSMO-RS) parameters, which was after applied in the estimation of the eutectic points of new ternary DES. The predictions quality was checked experimentally, proving that COSMO-RS can be a useful tool for the design of deep eutectic solvents.